MIND MAPPING AND EVERYBODY WRITES TECHNIQUES FOR STUDENTS WITH HIGH AND LOW WRITING ACHIEVEMENT (English Education Journal, 2014)
This research investigated the effectiveness of Mind Mapping and Everybody Writes techniques used for students with high and low writing achievement. The subjects of the study were the seventh graders of State Islamic Junior High School of Slawi Tegal in the academic year of 2013/2014. Two of fifteen classes in the school were selected as the samples of the research.The experiment was set up according to a pretest and posttest for both groups. The experimental research with factorial design 2x2 was used by using technique of multifactor analysis of variance (ANOVA). The finding of this research indicates that Mind Mapping and Everybody Writes techniques are effective and significant for students with high and low writing achievement. Everybody Writes teachnique is more effective than Mind Mapping technique for teaching writing. There is an interaction among writing skill, techniques and students’ achievement. This research finding can be seen from the results of the pretest and posttest that is very significant.